Continental drift triggered the Early Permian aridification of North China - Qiang Ren; Shihong Zhang; Mingcai Hou; Dongyu Zheng; Huaichun Wu; Tianshui Yang; Haiyan Li; Anqing Chen; James G. Ogg (Nature Communications)
Abstract The boundary between wet and arid climate zones in the Tethys Ocean remains challenging to trace, complicating our understanding of global aridification pattern during the Late Carboniferous to Early Permian transition. The North China Block (NCB), situated in the Tethys Ocean, underwent a transition from humid to arid climate during the Early Permian, providing a rare opportunity to trace this climate boundary across this region. Here, we present paleomagnetic evidence indicating that the NCB underwent rapid northward drift between 290 and 281 million years ago. The NCB’s movement from a tropical wet to a subtropical arid zone corresponds to a lithological change from coal-bearing to red-bed deposits, demonstrating tectonic drift into a subtropical arid zone as the main driver of aridification in the NCB during this period. This drift also delineates the wet–dry boundary over the Tethys Ocean, consistent with modern climatic zonation patterns.